Synthesis and potential applications of silicon carbide nanomaterials / nanocomposites. Issue 22 (15th November 2022) - Sun, Kaidi; Wang, Tongtong; Gong, Weibo; Lu, Wenyang; He, Xin; Eddings, Eric G.; Fan, Maohong
Abstract: The rapid development of nanotechnologies has accelerated the research in silicon carbide (SiC) nanomaterial synthesis and application. SiC nanomaterials have unique chemical and physical properties, such as distinctive electronic and optical properties, good chemical resistance, high thermal stability, and low dimensionality. These properties lead to a wide range of applications. The progress in SiC nanomaterials in recent years is significant, but a review of the progress is lacking. This article is designed to fill the gap. The review first summarizes various methods for preparing different SiC nanomaterials/nanocomposites, including the carbothermal method, chemical vapor deposition method, and other synthesis techniques using unconventional energy sources such as microwave, plasma, solar energy, and neutron irradiation. Discussion is then made on the significant applications of the SiC nanomaterials/nanocomposites, especially in sensors, catalyst supports, energy storage materials, structural reinforcement, and semiconductor materials. Finally, the conclusion of this review is made with the possible future development trends.